2013
DOI: 10.1111/gwat.12122
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting a Pumping Test Influenced by Another Well in an Anisotropic Aquifer

Abstract: In confined aquifers the influence of neighboring active wells is often neglected when interpreting a pumping test. This can, however, lead to an erroneous interpretation of the pumping test data. This article presents simple methods to evaluate the transmissivity tensor and storativity of an anisotropic confined aquifer when there is an interfering well in the neighborhood of the tested well. Two methods have been developed depending on whether the tested well or the interfering well is the first in operation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…By regressing nearby water levels against known withdrawal rates at the subject well, the method also discounts potential interference resulting from competing groundwater withdrawals (Rushton 1985; Weber and Chapuis 2013; Weber et al 2014). Both examples presented here are near large municipal withdrawals, and the background variability in aquifer water levels was captured in the LTM datasets.…”
Section: Application Of the Thiem Solutionmentioning
confidence: 99%
“…By regressing nearby water levels against known withdrawal rates at the subject well, the method also discounts potential interference resulting from competing groundwater withdrawals (Rushton 1985; Weber and Chapuis 2013; Weber et al 2014). Both examples presented here are near large municipal withdrawals, and the background variability in aquifer water levels was captured in the LTM datasets.…”
Section: Application Of the Thiem Solutionmentioning
confidence: 99%
“…The existing response function for aquifer pumping depends on specific information about pumping, such as pumping rates and spatial distribution. In previous literature (e.g., Rushton, 1985; Weber & Chapuis, 2013; Weber et al., 2014), it has been found that employing typical analytical solutions (like Theis (1935) solution or Jacob and Lohman (1952) approximate solution) to describe single‐well pumping activities applied to field data can lead to incorrect parameter estimation values in many areas with interfering wells. To achieve more accurate parameter estimations, it is essential to first obtain the pumping rates of interfering wells and the duration of pumping for each well (Weber & Chapuis, 2013).…”
Section: Introductionmentioning
confidence: 99%